Small RNA and its application in andrology and urology - Wang, Ji (AME Publishing Company, 2012)
Small non-coding RNAs such as small interfering RNA (siRNA), microRNA (miRNA) and piwi-interacting RNA (piRNA) exist in almost all kingdoms of organisms and have recently emerged as master regulators of gene expression to affect a diverse range of important biological processes. They exert their functions largely through two related but opposing mechanisms: RNA interference (RNAi) mediated by siRNA, miRNA and piRNA, and RNA activation (RNAa) mediated by small activating RNA (saRNA) and miRNA, leading to silencing and overexpression of target genes respectively. Dysregulation of these mechanisms have been implicated in a variety of human diseases including urological and andrological diseases. Importantly, both mechanisms can be readily harnessed for therapeutic purposes for a variety of diseases by using small RNA molecules as the "ribodrug". In this review, we highlight recent advances in the applications of small RNA as therapeutics for urological cancer, male infertile and erectile dysfunction.